Amigas e amigos no amigo : uma cristologia comunicativa da amizade em tempos digitais e de pandemia - Silva, Aline Amaro da (2021)
The present doctoral thesis, entitled "Friends in the Friend: A Communicative Christology of Friendship in Digital and Pandemic Times," investigates the perception of Catholic youth concerning Jesus Christ in order to think about a Christology that is adequate to the times of a digital culture marked by the experience of the coronavirus pandemic. It uses as reference the Theology of Communication, Communicative Theology, and Cybertheology. It highlights the theoretical and methodological contribution of Communicative Theology for the elaboration of this Christological study. Created in the dialogue between the systematic theology of Bernd Jochen Hilberath of the University of Tübingen, Germany, and the practical theology of Mathias Scharer of the University of Innsbrück, Austria, Communicative Theology emerges in the Germanic context as an interactive culture of theological doing. This research marks the debut of Communicative Theology in the Latin American and Brazilian theological scenario. A study of the theories and theologies of communication is developed in the first section. The practice of Communicative Theology with youth groups of the Emmaus Movement of Porto Alegre is described and analyzed in the second part. Through the interaction of the youth in online encounters, the importance of the relationship of Jesus Christ as friend of the digital youth is concluded. Therefore, a theological study on friendship is developed in order to build a communicative Christology of friendship. In a hyper-communicative society, paradoxically, we live the risk of isolation. In this way, humanity needs to rediscover itself with the hyper-communicative God, who has taken the initiative in dialoguing with its friends in the Friend. In this moment of physical distance, uncertainty and anxiety caused by the pandemic, Jesus approaches each young person as a friend more than a brother.